Anti-inflammatory activity of standardized dichloromethane extract of Salvia connivens on macrophages stimulated by LPS - Marco Martín González-Chávez; Cinthia Saraí Ramos-Velázquez; Roberto Serrano-Vega; Cuauhtemoc Pérez-González; Ernesto Sánchez-Mendoza; Salud Pérez-Gutiérrez (Taylor & Francis Group, 2017)
Context: A previous study demonstrated that the chloroform extract of Salvia connivens Epling (Lamiaceae) has anti-inflammatory activity. Objective: Identification of the active components in the dicholorometane extract (DESC), and, standardization of the extract based in ursolic acid. Material and methods: DESC was prepared by percolation with dichlromethane and after washed with hot hexane, its composition was determined by CG-MS and NMR, and standardized by HPLC. The anti-inflammatory activity was tested on acute TPA-induced mouse ear oedema at doses of 2.0 mg/ear. The cell viability of macrophages was evaluated by MTT method, and pro- and anti-inflammatory interleukin levels were measured using an ELISA kit. Results: Ursolic acid, oleanolic acid, dihydroursolic acid and eupatorin were identified in DESC, which was standardized based on the ursolic acid concentration (126 mg/g). The anti-inflammatory activities of DESC, the acid mixture, and eupatorin (2 mg/ear) were 60.55, 57.20 and 56.40% inhibition, respectively, on TPA-induced ear oedema. The IC50 of DESC on macrophages was 149.4 μg/mL. DESC (25 μg/mL) significantly reduced TNF-α (2.0-fold), IL-1β (2.2-fold) and IL-6 (2.0-fold) in macrophages stimulated with LPS and increased the production of IL-10 (1.9-fold). Discussion: Inflammation is a basic response to injuries, and macrophages are involved in triggering inflammation. Macrophage cells exhibit a response to LPS, inducing inflammatory mediators, and DESC inhibits the biosynthesis of the pro-inflammatory and promote anti-inflammatory cytokines. Conclusion: DESC has an anti-inflammatory effect; reduced the levels of IL-1β, Il-6 and TNF-α; and increases IL-10 in macrophages stimulated with LPS. Ursolic acid is a good phytochemical marker.